The Common Mistranslation of πρόσωπον πρὸς πρόσωπον “Face to Face” in 1 Cor 13.12b - Peterman, Gerald W. (The Bible translator, 2025)
In 1 Cor 13.12b, πρόσωπον πρὸς πρόσωπον is typically mistranslated with the English phrase “face to face.” Evidence in support of this includes: (1) The Hebrew behind πρόσωπον πρὸς πρόσωπον is פָּנִים אֶל־פָּנִים “face to face,” a metaphor that does not describe a physical encounter but an intimate verbal encounter. (2) The Greek is not natural but a Semitism deriving from the LXX of Gen 32.31(30) or Judg 6.22. (3) After the LXX, πρόσωπον πρὸς πρόσωπον does not take on its own life in Koine Greek. (4) The English phrase “face to face” refers to a literal encounter in someone else’s physical presence. (5) Paul had other natural Greek expressions available that would have communicated the physical encounter expressed by the English “face to face.” (6) We briefly consider how Greek readers or hearers of Paul’s letter might have understood πρόσωπον πρὸς πρόσωπον. (7) Translations of 1 Cor 13.12b should use the meaning of פָּנִים אֶל־פָּנִים. Translation options are given.